In Situ Electrochemical Activation Derived LixMoOy Nanorods as the Multifunctional Interlayer for Fast Kinetics Li‐S batteries. Issue 52 (12th November 2021) - Li, Tengyu; Li, Yanan; Yang, Jinlin; Deng, Yirui; Wu, Mengwei; Wang, Qi; Liu, Ruiping; Ge, Ben; Xie, Xiaokun; Ma, Jianmin
Abstract: Li‐S batteries (LSBs) have attracted worldwide attention owing to their characteristics of high theoretical energy density and low cost. However, the commercial promotion of LSBs is hindered by the irreversible capacity decay and short cycling life caused by the shuttle effect of lithium‐polysulfides (LiPSs). Herein, a hybrid interlayer consisting of MoO3, conductive Ni foam, and Super P is prepared to prevent the shuttle effect and catalyze the LiPSs conversion. MoO3 with a reversible lithiation/delithiation behavior between Li0.042 MoO3 and Li2 MoO4 within 1.7–2.8 V versus Li/Li + combines the Li + insertion and LiPSs immobilization and efficiently improve the LSBs redox kinetics. Benefiting from the reversible Li + insertion/extraction in lithium molybdate (Li x MoO y ) and the highly conductive Ni foam substrate, the sulfur cathode coupled with such electrochemical activation derived catalytic interlayer exhibits a high initial discharge capacity of 1100.1 mAh g −1 at a current density of 1 C with a low decay rate of 0.09% cycle −1 . Good capacity retention can still be obtained even the areal sulfur loading is increased to 13.28 mg cm −2 . Abstract : LMO/SP/NF interlayer brings about a new catalytic strategy based on the original proposed lithiation/delithiation behavior triggered by overpotential driving force. This behavior allows the Li + from the dissociated LiPSs species to diffuse on both the surface and bulk channels in the catalysts and thus accelerate the Li‐S reaction kinetics.